PENGARUH INFLASI, SUKU BUNGA, NILAI TUKAR/KURS, DAN IHSG TERHADAP HARGA SAHAM SYARIAH PENDEKATAN ERROR CORRECTION MODEL - Ayus Ahmad Yusuf (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2014)
ABSTRACTThe purpose of this research is to analyze the short and long run relationship between four macro economic variables, inflation, interest rate, exchange rate, and JCI on Sharia Stock Price. The data for assessing this research are acquired from the monthly financial reports published by Bank Indonesia, Central Bureau of Statistics and Indonesia Stock Exchange from January 2006 to December 2013. The Method and statistical analysis in this research used stasionarity test, The Classical Assumptions Test, Cointegration Test, Error Correction Model Test and The Test Of Significance. The data analyzing performed by statistical data processing software Eviews 4.The research shows that partially there are a relationship negative between inflation, interest rate,and exchange rate on sharia stock price in the long term. And JCI positive effect on sharia stock  price. And than partially there are a relationship negative between inflation, interest rate and Exchange rate on sharia stock price in the short term. While JCI positive effect on sharia stock price in the short term. Simultaneous there are a relationship between inflation, interest rate, exchange rate and JCI on Sharia Stock Price in the long trem and short term.  It’s mean macro variables can be used to  perdic movements sharia stock price in the long term and short term.Key Word : Inflation, Interest Rate, Exchange Rate, JCI, Sharia Stock Price, Error Correction Model